Synthesis of ylidene derivatives of 4-amino-5-(4-tert-butylphenyl)-4H-1,2,4-triazole-3-thiol - I. I. Aksionova; O. I. Panasenko; E. G. Knysh (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
Aim. Modern medicine widely applies drugs from the group of 1,2,4-triazole (fluconazole, triazolam, alprazolam, letrozole and others) in the practice. This class of compounds has synthetic origin and a broad spectrum of biological activity, and is characterized by low toxicity. It is known that the presence of triazole ring in the molecule effects on the range and intensity of biological action.